Tunable and Durable Toughening of Polylactide Materials Via Reactive Extrusion. Issue 5 (15th October 2013) - Kfoury, Georgio; Hassouna, Fatima; Raquez, Jean‐Marie; Toniazzo, Valérie; Ruch, David; Dubois, Philippe
<x xml:space="preserve">Abstract</x> To tune the toughness of PLA, a novel pathway to chemically modify PLA via reactive extrusion in the presence of "reactive" PEG derivatives is proposed. PEG methyl ether methacrylate (MAPEG) and PEG methyl ether acrylate (AcrylPEG) are melt‐mixed and extruded with PLA in the presence of 2, 5‐dimethyl‐2, 5‐di(tert‐butylperoxy)hexane (L101) as a free‐radical initiator. Molecular characterization reveals that about 20 and 65%, respectively, of the initially introduced MAPEG and AcrylPEG can be grafted onto the PLA backbone. The plasticization effect is demonstrated by a significant decrease of the glass transition temperature and storage modulus together with a significant increase of the elongation at break as compared to neat PLA.<inline-graphic xlink:href="ark:/27927/pgg5nq989qr" content-type="mame201300265-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />